Pengaruh Tekanan, Kesempatan, dan Rasionalisasi Terhadap Kecurangan (Fraud) Laporan Keuangan - Nandia Kurniawati; Aris Eddy Sarwono (Universitas Warmadewa, 2024)
This study aims to determine the effect of pressure, opportunity, and rationalization on fraud on financial statements. The type of data in this study is secondary data obtained from the Indonesian Brsa Efek (IDX) website. The population of this study is in transportation sub-sector companies listed on the IDX. The sampling method uses purposive sampling with the number of samples obtained, which is 9 samples in this study. The population of this study is in transportation sub-sector companies listed on the IDX. The sampling method uses purposive sampling with the number of samples obtained, which is 9 samples in this study. The analysis technique used is panel data regression. The results of this study show that pressure has a positive effect on financial statement fraud, opportunity has a positive effect on financial statement fraud, and rationalization has a negative effect on financial statement fraud.